KODE-KODE DALAM PUJIAN DAN PENYEMBAHAN IBADAH KARISMATIK - TAMENGGE, STELA MARIS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research which is entitled â€œKode-kode Dalam Pujian dan Penyembahan Ibadah Karismatikâ€ focuses on codes that can be found in almost all aspects of human life. In this category, codes are used in charismatic worship. The aims of this research are to identify and classify kinds of codes and to analyze and describe, meanings of codes that can be found in charismatic worship.Â The writer uses Peirceâ€™s theory about signs and codes (in Noth 1955)Â in the process of identifying and classifying kinds of codes and the process of analyzing and describing the meanings of codes used in charismatic worship. The data were collected in Mawar Sharon Tower of Strength Church Manado. The writer uses descriptive method to analyze the forms of codes found in charismatic worship activities in this research. The results of this research show that there are 22 codes used in charismatic worship. The writer classifies them into 2 parts; the first part is song map codes, which consist of 16 codes: verse, 3 times repetition before ending, 2 times repetition before ending, last repetition before ending, ending, overtune, lowertune, cooling down, overtune+chorus, overtune+3 times repetition before ending, full music, prechorus, solo drum, solo piano. The second part is key tone codes, which consist of 7 codes: key C, key D, key E, key F, key G, key A, key B. The meaning of the song map codes is to communicate with the praise and worship team to lead the song to be sung from different parts. The meanings of the key tones codes are to give and to change the key tones that are used in worship. Â Keywords: Charismatic Worship, Codes, Signs,Â Descriptive Method